Drought and Nitrogen Application Modulate the Morphological and Physiological Responses of Dalbergia odorifera to Different Niche Neighbors - Xiang, Li-Shan; Miao, Ling-Feng; Yang, Fan (Frontiers in Plant Science, 2021)
Mixed stands can be more productive if growth facilitation via niche segregation occurs. Dalbergia odorifera T. Chen, a tropical tree species endemic to Hainan Island that has great economic values, belongs to the family Leguminosae. However, selecting mixed species with suitable ecological niche to efficiently construct mixed forests of D. odorifera in the context of abiotic stress (drought, N deposition) remained obscure. In the present study, the target plant D. odorifera was planted with the same species D. odorifera, heterogeneous but the same Family Delonix regia, and non-Leguminous Family Swietenia mahagoni in the root interaction and isolated models under two watering regimes (100% and 30% field capacity [FC]) and two nitrogen applications (application, non-application), respectively. Principle component analysis on the basis of the performances of growth, phenotype and physiology was performed to identify the main factors affected by the treatments and the most discriminatory effects of water, N level and species interaction models. Both comprehensive evaluation values and comprehensive index values were calculated to evaluate the influence of different niche neighbors on D. odorifera. Results showed that D. odorifera was benefited from S. macrophylla but inhibited from D. odorifera in all treatments under root system interaction. Drought stress aggravated the inhibitory effects on D. odorifera from D. odorifera. N application stimulated the promoted effects on D. odorifera from S. macrophylla but enhanced competition intensity of D. odorifera from D. regia under the 100% FC condition. N application alleviated the inhibitory effect of drought stress on D. odorifera from D. odorifera and S. macrophylla. Furthermore, the responses of D. odorifera to different niche neighbors were dominated by belowground interaction rather than the negligible aboveground one. Therefore, the feasibility of a niche segregation as the criterion for selecting neighbors in construction of D. odorifera mixed stands was confirmed. In addition, water level and N application could alter responses of D. odorifera to different niche neighbors under the root system interaction. Appropriate N application could alleviate the inhibitory effect of drought stress on D. odorifera in its mixed forests. Mixture with S. macrophylla under appropriate N application could be the optimal planting model